The last century in the history of Judah - Čapek, Filip, 1971-; Lipschitz, Oded (Atlanta : SBL Press, 2019)
"This collected volume is the result of international cooperation between researchers who, coming from different academic disciplines and having different viewpoints, have concentrated on a single common theme, the kingdom of Judah the seventh century BCE, in the last full century of its existence. Eleven essays develop the current ongoing discussion about Judah during this period and extend the debate to include further important insights in the fields of archaeology, history, cult, and the interpretation of Old Testament texts"--
The last century in the history of the kingdom of Judah : new data, new queries, new interpretations / Oded Lipschits, Filip C̆apek -- "The long seventh century BCE" : archaeological and historical perspectives / Oded Lipschits -- King Josiah between eclipse and rebirth : Judah of the 7th century BCE in history and literature / Filip C̆apek -- New evidence of Iron Age II fortifications at Tel Hebron / David Ben-Shlomo -- What kind of village is this? : buildings and agro-economic activities north-west of Jerusalem during the iron IIB-C period / Yuval Gadot, Sivan Mizrahi, Liora Freud, David Gellman -- The widespread production and use of holemouth vessels in Jerusalem and its environs in the Iron Age II : typology, chronology, and distribution / Liora Freud -- Pictorial novelties in context : Assyrian iconography in Judah / Ido Koch -- Hezekiah's cultic reforms according to the archaeological evidence / David Rafael Moulis -- Through a glass darkly : figurines as a window on the past / Josef Mario Briffa SJ -- Prophetic books as a historical source for the monarchich period : the problem of historical reliability / Adam Mackerle -- The 7th century in the Book of Kings and the question of its first edition / Jan Rückl -- Two faces of Manasseh : the reception of Manasseh in the early Jewish literature / David Cielontko.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Bible. -- History of Biblical events; Bible. -- Criticism, interpretation, etc. -- History; Bible; Judaea (Region) -- History; Judaea (Region) -- Antiquities; Antiquities; History of Biblical events; Middle East -- Judaea Region; Criticism, interpretation, etc; History